Joomla! bible - SHREVES, Ric. (Indianapolis, IN : Wiley, 2010)
Joomla! is an open-source content management system (CMS) for web sites. While it is free and relatively easy to use, there are lots of tricks and functionality that may not be intuitive to new users or those switching from other systems. This title is a guide to everything Joomla!
Introduction -- Part I: Getting started with Joomla! -- Introducing the Joomla! content management system -- Obtaining and installing Joomla! -- Taking a look at Joomla! -- Getting the most from site configuration -- Part II: Working with content and users -- Managing content -- Working with editors and media -- Employing advanced content management techniques -- Working with the menu system -- Managing the front page of your site -- Working with the user manager -- Working with the language manager -- Part III: Working with components, modules, and plugins -- Using the Banner manager -- Working with the content manager -- Using the news feeds component -- Using the polls component -- Using the web links component -- Using the web links component -- Working with the site modules -- Working with the administrator modules -- Working with plugins -- Part IV: Customizing and extending the system -- Customizing Joomla! templates -- Customizing Joomla! functionality -- Extending your site -- Implementing e-commerce with VirtueMart -- Creating a community site with JomSocial -- Part V: Site maintenance and management -- Keeping your site secure and up to date -- Managing performance and accessibility -- Making a site search engine friendly -- Part VI: Appendixes -- Appendix A: The directory structure of a Joomla! installation -- Appendix B: A guide to the location of key files -- Appendix C: Installing XAMPP -- Appendix D: Installing MAMP -- Appendix E: Additional online help resources.
Includes index.
Keywords: Joomla! (Computer file); Web sites -- Authoring programs; Web site development; Open source software